In whose best interest? The Convention on the Rights of the Child and First Nations children. - Buenafe, Anne Caroline (Author); Woods, Lawrence (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 1997)
This thesis examines the Convention on the rights of the child and its application to First Nations children. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1151448